The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s40243-016-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of the iron on the surface of non-woven carbon fiber for use in a microbial fuel cell

Abstract: Iron particles were immobilized onto non-woven carbon fiber via electroplating for use in a microbial fuel cell (MFC). Electroplating was performed under an applied voltage at a current of 0.2 A for 5, 10, and 15 min. The scanning electron microscope (SEM) observations show that 5 min was not adequate for the particles to be immobilized, whereas 10 and 15 min of electroplating resulted in an adequate number of particles on the surface. To evaluate the strength of the binding of iron via electroplating on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The Nyquist plots of all three α-Fe 2 O 3 @CC electrodes had reduced interfacial electron transfer impedance compared to unmodified carbon cloth, with α-Fe 2 O 3 @CC-3 exhibiting the least resistance, confirming superior bioelectrocatalytic activity and potential for improved MFC performance. Post-analysis via live/dead bacterial staining and inverted fluorescence microscopy ( Supplementary Figure 2 ) showed higher bacterial counts on α-Fe 2 O 3 @CC electrodes compared to carbon cloth, with α-Fe 2 O 3 @CC-3 having the highest live bacteria count, indicating α-Fe 2 O 3 promotes bacterial adsorption and biofilm growth, aligning with previous findings( Ge et al, 2013 ; Phansroy et al, 2016 ; Mohamed et al, 2018 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The Nyquist plots of all three α-Fe 2 O 3 @CC electrodes had reduced interfacial electron transfer impedance compared to unmodified carbon cloth, with α-Fe 2 O 3 @CC-3 exhibiting the least resistance, confirming superior bioelectrocatalytic activity and potential for improved MFC performance. Post-analysis via live/dead bacterial staining and inverted fluorescence microscopy ( Supplementary Figure 2 ) showed higher bacterial counts on α-Fe 2 O 3 @CC electrodes compared to carbon cloth, with α-Fe 2 O 3 @CC-3 having the highest live bacteria count, indicating α-Fe 2 O 3 promotes bacterial adsorption and biofilm growth, aligning with previous findings( Ge et al, 2013 ; Phansroy et al, 2016 ; Mohamed et al, 2018 ).…”
Section: Resultssupporting
confidence: 89%
“…To enhance the performance of MFCs, researchers have modified the surfaces of diverse carbon-based electrode with iron oxides. For example, Fe 2 O 3 and Fe 3 O 4 electroplated non-woven carbon fiber anode facilitated the immobilization of S. oneidensis MR-1 on the electrode and promoted biofilm formation, thereby improving the performance of the MFC ( Phansroy et al, 2016 ). It has been demonstrated that Fe/Fe 2 O 3 nanoparticles deposited on carbon felt, carbon cloth and graphite led to a significant increase in power generation, which attributed to the improved wettability of the electrode surface for enhanced adhesion between the microbial community and the modified electrode surface ( Mohamed et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-felt (GF) electrodes are most commonly used in S-MFCs [ 4 , 23 , 24 ]. In addition to conductivity, corrosion resistance and ease of handling also contribute to the suitability of the CF electrode [ 25 ] for use in the soil–water environment. So far, both the cathode and anode of S-MFCs are mainly made of carbon-based materials, such as carbon brush, carbon cloth, carbon felt, graphite rods, and granulated carbon.…”
Section: Introductionmentioning
confidence: 99%